Orphans and discrimination in Mozambique: an outlay equivalence analysis - Nhate, Virgulino; Arndt, Channing; Barslund, Mikkel; Van den Broeck, Katleen (International Food Policy Research Institute, 2005)
The present study employs Deaton’s outlay equivalence approach to analyze potential discrimination in resource allocation within households against children who are not the biological descendant of the household head in Mozambique. High HIV prevalence in Mozambique motivates the study. The projected 800,000 AIDS related adult deaths over the period 2004-2010 will leave significant numbers of orphans in their wake. Of these, many will reside in families where the household head is not their biological parent. Results point to discrimination in the intra-household allocation of resources against children that are not direct biological descendants of the household head in poor households. This discrimination is identified at the national, rural, and urban levels In non-poor households, resource allocations between biological and non-biological children do not differ significantly.